2018
DOI: 10.1093/jn/nxx073
|View full text |Cite
|
Sign up to set email alerts
|

Corticosterone-Induced Lipogenesis Activation and Lipophagy Inhibition in Chicken Liver Are Alleviated by Maternal Betaine Supplementation

Abstract: These results indicate that maternal betaine supplementation protects male juvenile chickens from CORT-induced TG accumulation in the liver via epigenetic modulation of lipogenic and lipophagic genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 58 publications
4
29
0
Order By: Relevance
“…Plasma activity of alanine aminotransferase (ALT) and aspartate aminotransferase (AST), and the levels of triglycerides (TG), total cholesterol (TCHOL), high-and low-density lipoprotein cholesterol (HDL and LDL, respectively), and glucose (GLU) were analyzed using an automatic biochemical analyzer (7020, HITACHI, Tokyo, Japan), as previously described [22]. Hepatic triglycerides were measured using a tissue triglyceride assay kit (E1013; Applygen Technologies Inc., Beijing, China) as previously described [8].…”
Section: Plasma Biochemical Indicators Measurement and Triglycerides mentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma activity of alanine aminotransferase (ALT) and aspartate aminotransferase (AST), and the levels of triglycerides (TG), total cholesterol (TCHOL), high-and low-density lipoprotein cholesterol (HDL and LDL, respectively), and glucose (GLU) were analyzed using an automatic biochemical analyzer (7020, HITACHI, Tokyo, Japan), as previously described [22]. Hepatic triglycerides were measured using a tissue triglyceride assay kit (E1013; Applygen Technologies Inc., Beijing, China) as previously described [8].…”
Section: Plasma Biochemical Indicators Measurement and Triglycerides mentioning
confidence: 99%
“…It has been demonstrated that excessive glucocorticoid (GC) exposure can cause metabolic syndrome, including fatty liver disease, in both mammals and birds [7]. The active form of GC in chickens is primarily corticosterone (CORT), an indicator of stress [8]. Moreover, it is well known that treatment with exogenous CORT can cause abnormal fat deposition in the liver [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, controlling lipid accumulation in the liver can prevent the progression of lipid metabolic disorders [22]. In this study, fatty liver disease was mimicked in broilers by consecutive injection of CORT, showing with the typical characteristics of fatty liver disease as the previous report [10]. However, our results showed that probiotics supplementation from post-hatching for 2 weeks could effectively protect the lost of body weight, and prevent the progress of fatty liver disease induced by CORT in broilers.…”
Section: Discussionmentioning
confidence: 45%
“…However, our results showed that probiotics supplementation from post-hatching for 2 weeks could effectively protect the lost of body weight, and prevent the progress of fatty liver disease induced by CORT in broilers. It's reported that chronic CORT treatment reduces protein synthesis but promotes protein degradation, and nally leading to the loss of body weight in chickens [10,23]. It has been described that probiotic exhibits bene cial effect on body weight gain [24,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation